Development of an Advance Organizer Learning Model Based on Mind Maps to Increase the Meaningfulness of High School Student Learning in Pangkep Regency - Majid, Abdul Majid (International Journal of Curriculum Development, Teaching and Learning Innovation, 2023)
Based advance organizer learning model (PAO PaPi Model) for senior high school students. The research question is whether the development of PAO PaPi model is valid in terms of the theoretical basis and learning model components. The research subjects were 33 students in Senior High School 20 Pangkep, Indonesia. The development procedure of PAO Papi Model was carried out by referring to the development model of Plomp [1] which consists of five stages, namely: (1) investigation, (2) design, (3) realization / construction, (4) testing, evaluation and revision, and (5) implementation. The research product is the PAO PaPi Model. The component model developed refers to Joyce, et al. [2]. Characteristics of the developed model refer to Arend (2012), and product quality criteria refer to Nieeven (2007). Validation data analysis refers to Nurdin (2007) and Asdar (2013). The instrument reliability percentage used the concept of percentage of agreements by Grinnell (1988) in Nurdin (2007). The results showed that the PAO PaPi model was valid in terms of the supporting theories and components of the model